2016
DOI: 10.1159/000447831
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia/Reperfusion Injury Alters Sphingolipid Metabolism in the Gut

Abstract: Background: Intestinal ischemia/reperfusion injury (I/R) is a significant cause of morbidity and mortality in surgical patients. Ceramide is a mediator of apoptosis and has been implicated as increasing bacterial infection susceptibility. The metabolite of ceramide, sphingosine, was recently shown to play an important role in the cell-autonomous, innate immune response of the upper respiratory tract by killing bacterial pathogens. The role of ceramide and/or sphingosine after mesenteric I/R is unknown. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…In recent years, research hotspots focus on energy metabolism disorder, reactive oxygen, signaling pathways, etc. There into, energy metabolism disorder is considered to be the initiation link of RIRI, while the signaling pathway of NO/cGMP/PKG, all which [NO, cGMP and PKG (cGMP-dependent protein kinase)] play important biological functions in a variety of histocytes, is considered as the key link to induce IRI [29-31]. PKG is an extensively existed serine/threonine kinase in eukaryocytes, while cGMP plays the role as the second messenger through the interaction between intracellular receptor proteins, in which the most key receptor of cGMP in the vascular smooth muscle cells is serine/threonine kinase (i.e., PKG) [32].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research hotspots focus on energy metabolism disorder, reactive oxygen, signaling pathways, etc. There into, energy metabolism disorder is considered to be the initiation link of RIRI, while the signaling pathway of NO/cGMP/PKG, all which [NO, cGMP and PKG (cGMP-dependent protein kinase)] play important biological functions in a variety of histocytes, is considered as the key link to induce IRI [29-31]. PKG is an extensively existed serine/threonine kinase in eukaryocytes, while cGMP plays the role as the second messenger through the interaction between intracellular receptor proteins, in which the most key receptor of cGMP in the vascular smooth muscle cells is serine/threonine kinase (i.e., PKG) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis is a form of programmed cell death that is controlled by death signals and displays a death pattern like that of necrosis [98]. Local ischemia is caused by obstruction of blood flow to tissue, resulting in a limited supply of oxygen and nutrients, which if prolonged, can impair energy metabolism and cell death [99]. The recovery of blood loss (reperfusion) leads to the reintroduction of oxygen and the production of ROS, leading to cell death associated with inactivation [100, 101].…”
Section: Necrosis and Necroptosismentioning
confidence: 99%
“…Recent study has demonstrated that I/R injury altered sphingolipid metabolism in the intestine [40]. Moreover, regulation of cell communication, ROS biosynthesis and multiple signaling pathways such as cGMP-PKG, cAMP, MAPK and PPAR were identified in the iPoC group compared with the I/R group, suggesting that related coding genes may play crucial roles in iPoC-mediated protection against intestinal I/R injury through regulating the above mentioned biological mechanisms and signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%